A Contested Hegemon? Germany's Leadership in EU Relations with Russia. Issue 1 (2nd January 2020) - Siddi, Marco
Abstract : This article investigates Germany's role in the European Union's (EU) foreign policy towards Russia. It argues that Germany has been a leader in EU relations with Russia since the late 2000s, most notably through attempts to upload its long-standing policy of dialogue and cooperation with Moscow – known as Ostpolitik – to the EU level. During the Ukraine crisis, German leadership in this field became hegemonic. Economic and institutional power, the consent of its European and transatlantic allies and supportive domestic politics allowed Germany to profile itself as the main EU negotiating partner for Moscow. By highlighting the long-term German quest for leadership in the EU's relations with Russia, the article makes the argument that Germany is not a 'reluctant', but rather an assertive hegemon in this policy area. Furthermore, the article highlights how the Ostpolitik tradition and its self-conception as a civilian power enabled Germany to lead Western diplomacy in the Ukraine crisis. At the same time, Germany's hegemonic leadership in EU-Russia relations faces several challenges and limitations, which relate to the nature of Germany's power, the consent of its allies and evolving domestic politics.